Al-Manar Magazine's Stance on the Iran-Iraq War for the Period(1980-1988) - Abd al-Rasul Jabr Abbas , Lect . Dr. Ahmad (Basra studies journal, 2026)
Newspapers and magazines have often chronicled and covered various events, offering political insights and analyses. Among them was Al-Manar magazine, launched in Paris in 1985. The magazine was distinguished by its comprehensiveness, covering political, economic, cultural, and social topics. It studied and analyzed the Iran-Iraq War, which raged between 1980 and 1988, even though its first issue was published in January 1985. The topics covered in its pages were diverse, with political, social, and cultural aspects receiving the most attention. Al-Manar magazine followed a crucial and vital topic: the Iran-Iraq War (1980-1988). The war was not a spontaneous event but rather stemmed from border disputes between the two countries, in addition to the significant impact of political problems on its outbreak. Iraq attempted to nullify the 1979 Algiers Agreement with Iran, exploiting the deteriorating internal situation in Iran following the success of the Islamic Revolution in 1979. Iraqi forces launched a surprise military attack on Iran on September 22, 1980, believing it would force the Iranian leadership to submit to their terms. However, these calculations proved wrong, leading to an eight-year war during which all international mediation efforts to end the war failed due to Iran's rejection of mediation, as well as the intervention of major powers who desired the continuation of the war to weaken the capabilities of both Iraq and Iran.